Factors affecting patient safety culture among dental healthcare workers: A nationwide cross-sectional survey - Hsin-Chung Cheng; Amy Ming-Fang Yen; Yi-Hsuan Lee (Journal of Dental Sciences, 2019)
Background/purpose: Patient safety is a major healthcare challenge. Due to a lack of safety culture knowledge among dental professionals, our objectives were to measure the level of patient safety culture using the Safety Attitude Questionnaire in Chinese (SAQ-C) and identify factors associated with positive attitudes toward patient safety. Materials and methods: A nationwide cross-sectional survey was conducted within dentistry departments of 20 hospitals and in 40 dental clinics, from which were randomly chosen. The survey (SAQ-C) comprised of 32 items and reflects five dimensions of patient safety culture. The second section collects demographic information that supposedly affects attitudes toward patient safety. Logistic regression analyses were used to identify factors that supposedly influenced positive attitudes toward patient safety. Results: Mean SAQ-C scores were significantly higher in respondents who were male, older, dentists, supervisors, and working in clinics. Positive attitudes toward patient safety were found in 172 participants (55.7%). Multivariate analyses revealed age and place of work are significantly associated with positive safety attitudes. A limitation of this study is that the association between SAQ-C scores and patient outcomes could not be examined. Conclusion: With a lack of research in the dental field, our study provides important information on patient safety attitudes for dental healthcare workers. Results from this study present the current status of patient safety culture and help raise awareness of it. Most notably, the study identified several factors associated with positive attitudes toward patient safety. The information can be used to improve patient safety in the future. Keywords: Cross-sectional study, Dental healthcare workers, Nationwide survey, Patient safety, Risk factors